Longitudinal Serial Mediation Relationship of Intolerance of Uncertainty, Irrational Happiness Beliefs and Mistake Rumination with Family Communication - Korun, Ali Berke; Satici, Seydi Ahmet (SPRINGER, 2025)
The family systems approach suggests that individuals' psychological processes are shaped within the framework of family interactions. Accordingly, the current study examines the long-term effects of intolerance of uncertainty, irrational happiness beliefs and mistake rumination on family communication within the scope of a semi-longitudinal model. The study analyzed the predictive power of intolerance of uncertainty on irrational happiness beliefs and mistake rumination and whether these variables play a mediating role in family communication. The study, which was conducted in two phases at five-month intervals, included 325 adult participants aged 18-51. Longitudinal serial mediation analysis revealed that intolerance of uncertainty increases irrational happiness beliefs and mistake rumination over time, and these processes negatively affect family communication. The findings suggest that individuals' low tolerance for uncertainty may shape long-term psychological and relational dynamics through family interactions. The study emphasizes the importance of holistic interventions to support the functionality of family systems. In particular, it is suggested that short-term systemic family therapy and emotion-focused individual interventions may be effective in strengthening family communication and increasing the psychological resilience of individuals.
Keywords: Intolerance of uncertainty; Irrational happiness beliefs; Mistake rumination; Family communication; Longitudinal; ROLES; Psychiatry